Advanced Hepatocellular Carcinoma With Hepatic Arterioportal Shunts: Combination Treatment of Transarterial Chemoembolization With Apatinib - Sun, Tao; Ren, Yanqiao; Kan, Xuefeng; Chen, Lei; Zhang, Weihua; Yang, Fan; Zheng, Chuansheng (Frontiers in Molecular Biosciences, 2020)
Object: This study aimed to compare the efficacy and safety of transarterial chemoembolization (TACE) combining with apatinib (TACE-apatinib) and TACE-alone for patients with advanced hepatocellular carcinoma (HCC) with hepatic arterioportal shunts (APS). Materials and Methods: This retrospective study evaluated the medical records of patients with advanced HCC with APS who underwent TACE-apatinib or TACE-alone from June 2015 to January 2019. The occlusion of the shunt was performed during the TACE procedure. The time to tumor progression (TTP) and overall survival (OS) of study patients were evaluated. The modified Response Evaluation Criteria in solid tumors (mRECIST) was used to evaluate the treatment response. The apatinib-related adverse events were recorded. Results: Fifty-eight patients were included in this study. Twenty-seven patients underwent the treatment of TACE-apatinib, and 31 received TACE-alone treatment. The median overall survival (OS) and median time of tumor progression (TTP) in the TACE-apatinib group were significantly longer than those of the TACE-alone group (OS: 12.0 vs. 9.0 months, P = 0.000; TTP: 9.0 vs. 5.0 months, P = 0.041). Multivariate analysis revealed that TACE-apatinib was a protective factor for OS, and there was no independent risk factor for TTP. In the TACE-apatinib group, the grade 3 apatinib-related adverse events occurred in four patients. Conclusion: TACE-apatinib was an efficacious and safe treatment for patients with advanced HCC with APS, and apatinib improved the efficacy of TACE in the treatment of these patients.